THE IMPLEMENTATION OF MERDEKA BELAJAR – KAMPUS MERDEKA IN INDONESIAN HIGHER EDUCATION - Ira Arini; Fariza Hashim; Lintang Rizkyta Ananda; Samsu Bahri (Prosiding Amal Insani Foundation, 2026)
The Kampus Mengajar (Teaching Campus) program is part of the Merdeka Belajar–Kampus Merdeka (Freedom of Learning) policy initiated by the Ministry of Education, Culture, Research, and Technology of the Republic of Indonesia as an effort to transform learning in Indonesian higher education. This program aims to provide contextual learning experiences to students through direct involvement in strengthening literacy, numeracy, technology adaptation, and educational administration in primary and secondary education units. This study aims to analyze the implementation of the Kampus Mengajar (Teaching Campus) program in Indonesian higher education, identifying achievements, challenges, and its implications for student competency development. The study used a qualitative descriptive method with a systematic literature review (SLR) approach. Data were collected through searches of national and international indexed scientific articles, proceedings, and official policy reports relevant to the period 2020–2025. The analysis process was carried out through the stages of identification, selection, quality evaluation, data extraction, and synthesis of findings. The results of the study indicate that the implementation of Kampus Mengajar has a positive impact on improving students' pedagogical, social, leadership, and digital literacy competencies. In addition, this program contributes to strengthening the profile of adaptive and collaborative graduates. However, several obstacles were identified, including institutional readiness, coordination between universities and partner schools, and administrative and technical challenges in the field. This study concludes that Kampus Mengajar (Teaching Campus) is a relevant policy innovation in promoting experiential learning in higher education, but requires strengthening the governance system and ongoing evaluation to improve its implementation effectiveness